LITTER BIOMASS AND CARBON STORAGE IN PRIA LAOT WATERFALL TOURISM AREA, BATEE SHOEK VILLAGE, SABANG - Anita, Seri; Jamaluddinsyah (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Differences in climate and human activities, such as deforestation and intensive agriculture, can increase litter carbon emissions, thereby contributing to global warming. Waterfall tourism areas possess vegetation characteristics that differ from those of natural forests, making it essential to analyze litter biomass and carbon storage in Pria Laot Waterfall Tourism Area, Sabang City. This study employed a purposive sampling method using transect lines and plots to determine litter biomass, carbon storage, and the environmental parameters influencing these factors. The results showed that the total litter biomass in Pria Laot Waterfall Area, Batee Shoek, Sabang, reached 6.47 kg, with an average of 1.32 kg per transect. Transect 3 exhibited the highest litter biomass (3.52 kg), while Transect 1 recorded the lowest (0.99 kg). The total stored litter carbon in the area was 0.253 kg, with an average of 0.084 kg per transect. Transect 3 also had the highest litter carbon (0.138 kg), whereas Transect 1 had the lowest (0.039 kg). The litter carbon storage in the area amounted to 2.53 tons/ha, with Transect 3 showing the highest value (1.38 tons/ha) and Transect 1 the lowest (0.39 tons/ha). The study concludes that variations exist in litter biomass and carbon storage across transects, where transects located near settlements exhibited higher biomass and carbon storage. These findings indicate that environmental factors play a crucial role in determining litter and carbon distribution.